2022
DOI: 10.1007/s11356-022-19433-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of controlled migration of cadmium and lead into foods from plastic utensils for children

Abstract: Lead is a highly neurotoxic chemical element known for reducing intelligence quotient (IQ) and promoting antisocial behavior in children and adolescents, while cadmium is a carcinogenic bioaccumulative element. Contaminated foods and beverages are the most common routes of exposure. The objective of this study was to determine Cd and Pb concentrations in colored plastic utensils for use by children and to measure the speci c migration of these elements into beverages and foods. Pb and Cd concentrations were de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Furthermore, wastewater carrying industrial wastes that may be used to irrigate agricultural lands, the burning of fossil fuels such as coal or oil, and the incineration of municipal waste may be a major source of Cd in the food chain (Adedapo & Adeoye, 2014 ; Mahmood et al, 2019 ). Plastic utensils used for handling food have also been found to contaminate food with Cd (Pereira et al, 2022 ). Plastic utensils are common in street vending environments in the study area as reported earlier (Mwove et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, wastewater carrying industrial wastes that may be used to irrigate agricultural lands, the burning of fossil fuels such as coal or oil, and the incineration of municipal waste may be a major source of Cd in the food chain (Adedapo & Adeoye, 2014 ; Mahmood et al, 2019 ). Plastic utensils used for handling food have also been found to contaminate food with Cd (Pereira et al, 2022 ). Plastic utensils are common in street vending environments in the study area as reported earlier (Mwove et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Contamination may occur at any step from the production of raw materials to street food preparation and eventual vending (Proietti et al, 2014 ). It has been reported that the use of unsuitable cookware, utensils, and food packaging material could release harmful chemicals such as heavy metals into the food (Letuka et al, 2023 ; Pereira et al, 2022 ). In addition, the source of raw food products and exposure to environmental contaminants, such as vehicle exhaust emissions and airborne dust particles may cause contamination of food with heavy metals (Ali & Al‐Qahtani, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have been raised about the potential for metal migration from these utensils into the food and beverages they come into contact with, which could result in health risks for consumers. This research aims to investigate the impact of electroplating on the migration of metals from utensils and assess the potential health risks associated with such migration [20][21][22][23][24][25][26][27][28][29][30][31] .…”
Section: Graph 2 Line Graph Illustrating the Impact Of Electroplating...mentioning
confidence: 99%
“…15 As a result of the above, there is an increasing need to develop methods based on the principles of green analytical chemistry (GAC). 16 From the GAC perspective, direct non-destructive analytical methods such as X-ray uorescence spectroscopy (XRF), 17 neutron activation analysis (NAA), 18 or even the destructive direct solid sampling (DSS) technique, 19,20 can be used for the metal analysis of solid plastics samples; these do not require any treatment of the solid sample. However, these methods have a problem with the representativeness of the analysed sample, inhomogeneity of the samples, matrix effects, calibration standards and availability of certied reference materials (CRMs).…”
Section: Introductionmentioning
confidence: 99%